Discrimination of debris flow in narrow-steep type and wide-gentle type gullies in Wenchuan meizoseismal area - Xu, Guoqing; Ji, Jiejie; Luo, Dengze; Qi, Shunchao; Li, Hongtao; Dembele, Molobaly Dit Mahamadou; Yao, Qiang (Frontiers in Earth Science, 2023)
The debris flow disasters in the Wenchuan meizoseismal area are dominantly triggered by the gully-type debris flow. Research on its classification method can be of great theoretical value and practical significance for developing targeted prevention measures. The current empirical classification method has some disadvantages, such as inconsistent discrimination criteria and poor practicability. In this paper, in order to overcome these drawbacks, the topography, rainfall, and source characteristics data of 176 gully-type debris flows in the Wenchuan “5.12” meizoseismal area since 2008 were collected and divided into the narrow-steep, transitional, and wide-gentle types based on field investigation. The narrow-steep type gullies are mainly concentrated in small catchments with severe erosion. In contrast, the wide-gentle type gullies are often characterized by big catchments, gentle vertical slopes, and debris flows movement dominated by deposition. An empirical discrimination method for debris flow gullies is proposed based on the characters of the gullies in the meizoseismal area, and a mathematical discrimination model named Gully Geomorphology Index (GGI) is also constructed. The results from existing cases indicated that both methods were accurate to discriminate between the narrow-steep and wide-gentle debris flow gullies. According to the empirical discrimination method, among the 176 channel-type debris flows, the numbers of narrow-steep, transitional, and wide-gentle channel types are 105 (59.66%), 12 (6.82%), and 59 (33.52%), respectively. While for the GGI method, the value 0.05 and 0.10 were defined as the threshold of the three types, and the distribution of the results is 104 (59.09%) for the narrow-steep type, 16 (9.09%) for the transitional type, and 56 (31.82%) for the narrow-steep type, which can better classify the transitional type gullies and is more practical. We hope that the discrimination methods proposed in this paper will help better understand the disaster-causing mechanism and improve the prevention measures of debris flow in the Wenchuan meizoseismal area.